Feminist Collections, v.32, no.2 (spring 2011) - (:unkn) unknown (My University, 2011)
Subtitle: A Quarterly of Women's Studies Resources, ISSN 0742-7441, 38p.
Contents: From the Editors: A Bookstore of One's Own, by JoAnne Lehman Book Reviews: "Critics on Caribbean Women Writers of Fiction," by Consuelo Lopez Springfield. (Reviews Brinda Mehta, NOTIONS OF IDENTITY, DIASPORA, AND GENDER IN CARIBBEAN WOMEN'S WRITING, New York: Palgrave Macmillan, 2009; Florence Ramond Jurney, REPRESENTATIONS OF THE ISLAND IN CARIBBEAN LITERATURE: CARIBBEAN WOMEN REDEFINE THEIR HOMELANDS, Lewiston, NY: Edwin Mellen Press, 2009; Chantal Kalisa, VIOLENCE IN FRANCOPHONE AFRICAN AND CARIBBEAN WOMEN'S LITERATURE, Omaha, NE: University of Nebraska Press, 2009; and Keshia N. Abraham, ed., THE CARIBBEAN WOMAN WRITER AS SCHOLAR: CREATING, IMAGINING, THEORIZING, Coconut Creek, FL: Caribbean Studies Press, 2009.) "Woman Defines Herself: (Re)Claiming Identity by Revisioning Theater and Revisiting History," by Autumn Shiley. (Reviews Sharon Friedman, ed., FEMINIST THEATRICAL REVISIONS OF CLASSIC WORKS: CRITICAL ESSAYS, Jefferson, NC: McFarland & Co., 2009; Lisa M. Anderson, BLACK FEMINISM IN CONTEMPORARY DRAMA, Urbana, IL: University of Illinois Press, 2008; Purnur Ucar-Ozbirinci, PLAYS BY WOMEN ABOUT WOMEN PLAY WRITERS: HOW WOMEN CREATE MYTHS ABOUT THEMSELVES, Lewiston, NY: Edwin Mellen Press, 2009; and Milly S. Barranger, UNFRIENDLY WITNESSES: GENDER, THEATER, AND FILM IN THE MCCARTHY ERA, Carbondale, IL: Southern Illinois University Press, 2008). FEMINIST VISIONS COLUMN "A Messiah for Women: Helping Girls Escape Abusive Marriage in India," by Madelyn Homuth, Heather Shimon, & Melissa A. Young. (Reviews PINK SARIS. 96 mins., directed by Kim Longinotto, 2010. In Hindi with English subtitles and distributed by Women Make Movies.) "Oldies by Goodies: Archiving Web-Based Information," by Phyllis Holman Weisbard E-Sources on Women and Gender NEW REFERENCE WORKS IN WOMEN'S STUDIES Mustafa F. Ozbilgin & Jawad Syed, eds., MANAGING GENDER DIVERSITY IN ASIA: A RESEARCH COMPANION, Northampton, MA: Edward Elgar Publishing, 2010. Reviewed by Erin Fields. Sara Gray, THE DICTIONARY OF BRITISH WOMEN ARTISTS. Cambridge, U.K.: Lutterworth Press, 2009. Reviewed by Nina Clements. Karen Bellenir, ed., CANCER SOURCEBOOK FOR WOMEN, 4th edition. Detroit, MI: Omnigraphics Press, 2010. Reviewed by Ann Marie Smeraldi. Dora Kohen, ed., OXFORD TEXTBOOK OF WOMEN AND MENTAL HEALTH. New York: Oxford University Press, 2010. Reviewed by Janet S. Fore. Ellen Kuhlmann & Ellen Annandale, eds., THE PALGRAVE HANDBOOK OF GENDER AND HEALTHCARE. New York: Palgrave Macmillan, 2010. Reviewed by Nancy Nyland. Nina Lykke, FEMINIST STUDIES: A GUIDE TO INTERSECTIONAL THEORY, METHODOLOGY AND WRITING. New York: Routledge, 2010. Reviewed by Juliann Couture. Kath Browne & Catherine J. Nash, QUEER METHODS AND METHODOLOGIES: INTERSECTING QUEER THEORIES AND SOCIAL SCIENCE RESEARCH. Burlington, VT: Ashgate Publishing, 2010. Reviewed by Evan Boyd. THE WORDS OF EXTRAORDINARY WOMEN, sel. & intr. by Carolyn Warner; fwd. by Justice Sandra Day O'Connor. New York: Newmarket Press, 2010. Reviewed by Bernice Redfern. David E. Newton, SAME-SEX MARRIAGE: A REFERENCE HANDBOOK. Santa Barbara, CA: ABC-CLIO, 2010, Reviewed by Kari D. Weaver. Nigel West, HISTORICAL DICTIONARY OF SEXSPIONAGE. Lanham, MD: Scarecrow Press, 2009. Reviewed by Rebecca Tolley-Stokes, Peter Aggleton & Richard Parker, eds., ROUTLEDGE HANDBOOK OF SEXUALITY, HEALTH AND RIGHTS. New York: Routledge, 2010. Reviewed by Susan Wood. Carlisle K. Webber, GAY, LESBIAN, BISEXUAL, TRANSGENDER AND QUESTIONING TEEN LITERATURE: A GUIDE TO READING INTERESTS. Santa Barbara, CA: Libraries Unlimited, 2010, Reviewed by Matthew Harrick. Michele A. Paludi, ed., FEMINISM AND WOMEN'S RIGHTS WORLDWIDE. Santa Barbara CA: Praeger, 2010. 3 vols.: Vol. I, Heritage, Roles, and Issues, Vol. II, Mental and Physical Health, Vol. III, Feminism as Human Rights. Reviewed by Susan Bennett White Clare Cushman, ed., SUPREME COURT DECISIONS AND WOMENS' RIGHTS: MILESTONES TO EQUALITY, SECOND EDITION, fwd. by Assoc. Justice Ruth Bader Ginsburg; spons. by Sup. Ct. Hist. Soc. Washington, DC: CQ Press/Sage, 2010. Reviewed by Amanda Swygart-Hobaugh. Jennine Hurl-Eamon, WOMEN'S ROLES IN EIGHTEENTH-CENTURY EUROPE. Denver, CO: ABC-CLIO/Greenwood, 2010. Reviewed by Melissa A. Young. Ruth Margolies Beitler & Angelica R. Martinez, WOMEN'S ROLES IN THE MIDDLE EAST AND NORTH AFRICA. Santa Barbara, CA: ABC-CLIO/Greenwood, 2010. Reviewed by Aryana Bates.
Keywords: Feminist Theater; Caribbean Women Writers; Feminist Bookstores; E-sources; Gulabi Gang; Marriage--India; Archiving Web-based information; Women's Studies; Gender; Feminism; Library Resources; Reviews